The effects of online reviews on service expectations: do cultural value orientations matter? - Nath, Prithwiraj; Devlin, James; Reid, Veronica (Elsevier, 2018)
This study aims to explore the moderating influence of cultural value orientations of consumers on their use of positive and negative electronic word of mouth eWOM (PWOM and NWOM) to develop service expectations. It uses two experimental studies. Study 1 involves analysis of the manipulated effects of consumer-generated eWOM valence with 266 consumers from three different countries. Study 2 comprises of replication of study 1 but with added marketer generated information (imagery of the firm) with 84 consumers. The findings show that cultural value dimensions of power distance and long-term orientation influence how consumers react to PWOM and NWOM. For low power distance and short-term oriented consumers, the degree of impact on expectations is much higher when they encounter NWOM versus PWOM as compared to high power distance and long-term oriented consumers. It suggests a new segmentation strategy for practitioners based on the relationship between the interpretation of online reviews and cultural orientation of individual consumers.